Hubungan Intensitas Bermain Game Online dengan Tingkat Stress dan Kecerdasan Emopsional Remaja Pada Era New Normal - Ni Made Yeshika Armiandeni; Ni Luh Putu Dina Susanti; Ni Wayan Manik Parwati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
An online game is a game that can be accessed through electronic media connecting to an internet network. Addiction to playing online games has an impact on someone’s mental health namely stress and emotional intelligence. This study aimed to determine the correlation between the intensity of online game playing toward stress levels and emotional intelligence in the new normal era. This study was quantitative research with a correlational design. There were 157 adolescents who played an online game at Perumahan Griya Nugraha recruited as a sample of this study which was selected through convenience sampling. The data were collected using a questionnaire and analyzed using Spearman’s Rho test. The finding showed a positive correlation between the intensity of online game playing and stress level with p-value 0,001 dan r = 0,451. There was a negative correlation between the intensity of playing the online game and emotional intelligence with p-value 0,001 dan r = -0,550. it can be concluded that there is a correlation between the intensity of playing online games toward stress levels and emotional intelligence.